AI Tools in Improving Speaking Skills: A Literature Review - Ilma Sania Ramadhani; Khusnul Khotimah; Ratih Dwi Putri; Syahra Arisya (Journal in Teaching and Education Area, 2025)
This study is a systematic literature review that aims to examine the extent to which Artificial Intelligence (AI) and various AI tools are used to improve the speaking skills of English language learners. The main focus of this study is to identify the benefits of using AI in vocabulary, grammar, pronunciation, fluency, and student confidence, while also reviewing the challenges that accompany it, such as technological limitations, ethical issues, and accessibility problems. Based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, 960 articles published in 2025 from the ERIC database were reviewed, with 7 studies identified as most relevant for further analysis. The findings reveal that AI applications such as chatbots, speech recognition tools, and project-based learning models contribute to improving vocabulary, grammatical accuracy, pronunciation, fluency, and learners’ confidence. Moreover, integrating AI with project-based and blended learning approaches fosters collaboration, critical thinking, and more authentic language use. Nevertheless, several challenges remain, including overreliance on technology, reduced human interaction, as well as ethical and accessibility concerns. Therefore, while AI holds considerable promise in transforming speaking instruction, teachers continue to play a crucial role in providing pedagogical guidance, cultural sensitivity, and emotional support. The review also highlights the need for further research to evaluate the long-term impact of AI integration in language education..